Rule-based probabilistic learning and teaching of English prepositions: a cognitive corpus-based approach - Bączkowska, Anna (Scripta Neophilologica Posnaniensia, 2018)
Rule-based probabilistic learning and teaching of English prepositions: a cognitive corpus-based approach